Study on Land Use Activities and Their Effects on Soil Erosion on the Slopes of Kajulu Hills, Kisumu County, Kenya - J. Otieno; A. C. Otieno; K. W. Tonui (Modern Advances in Geography, Environment and Earth Sciences Vol. 4, 2021)
Soil erosion is a natural phenomenon, but human activities accelerate it between ten to forty times the natural occurrences. It therefore calls for mitigating measure to curb the effects of erosion since soils form at a slower rate than they are destroyed. A study on land use activities and their effects on soil erosion was conducted in the upland ecosystem in Kenya, Kajulu hills. The study assessed the effectiveness of the mitigation measures adopted by the residents to ease the effects erosion on the hill slopes. A sample size of 295 households out of 1600 households engaged in various mitigating practices was used. The study collected data on the magnitude of soil (kg) lost from the arable lands using collector ditch technique. The data were analyzed using frequency distribution tables and Man U-test. The result showed a double amount (1.198 kg/m2) of soil lost on the arable land without mitigation measures as compared to plots under cut off ditches (0.615 kg/m2) and vegetative strips (0.904 kg/m2) with Man U=7. These findings were above the world wide estimation of soil erosion on arable mountainous regions which range between 1.3-40.kg/m2/year (13-40T/Ha/year) as it was based on one rainy season. The findings showed that the mitigation measures adopted by the farmers to check the effects of soil erosion were effective with Man U=7 under the cut off ditches and vegetative strips.